KEEFEKTIFAN MODUL ELEKTRONIK BERBASIS KONSERVASI UNTUK MENINGKATKAN KREATIFITAS PEMBELAJARAN MATA KULIAH PANGKAS DISAIN - Erna Setyowati (Jurnal Ilmiah Pendidikan Teknik dan Kejuruan, 2018)
The conventional methods still used in practical learning of hairdressing subject and its gave the less optimal learning results. Its requires some creativity, extensive innovation and an electronic module containing materials, images and video tutorials, therefore self-learning stimulus could be provided optimally. Paperless method is one implementation of conservation policy of environmental efficiency and prevention of environmental pollution, beside that it could optimizing the information technology based system on the learning process. Conservation-based electronic module using C56 adobe flash software and flipbook application. The objective of this research is to know the effectiveness of electronic module based on conservation and improvement of learning creativity of hairdressing. The research used the pre-experiment design, observation data collection method, questionnaire, test and documentation with descriptive percentage analysis and validity module test. The result of module validity test is declared a feasible and effective equaled to 84,20 %, while the result of learning using electronic module was increasing student creativity equaled to 22,85 % which obtained from pre-test, post test and process based on aspect of science, affective, and skills assessment.